2023
DOI: 10.1002/mp.16583
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative performance of photon‐counting CT at low dose: Virtual monochromatic imaging and iodine quantification

Abstract: BackgroundQuantitative imaging techniques, such as virtual monochromatic imaging (VMI) and iodine quantification (IQ), have proven valuable diagnostic methods in several specific clinical tasks such as tumor and tissue differentiation. Recently, a new generation of computed tomography (CT) scanners equipped with photon‐counting detectors (PCD) has reached clinical status.PurposeThis work aimed to investigate the performance of a new photon‐counting CT (PC‐CT) in low‐dose quantitative imaging tasks, comparing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Future studies will be needed to find the optimal VMI energy for other abdominal pathologies and quantification tasks. 35 In conclusion, detectability of liver lesions depended on the radiation dose and phantom size and was considerably improved by selecting the optimal VMI energy. Based on our findings, we suggest VMI at 65 or 70 keV as the optimal VMI energy to detect hypoattenuating or hyperattenuating liver lesions.…”
Section: Discussionmentioning
confidence: 93%
“…Future studies will be needed to find the optimal VMI energy for other abdominal pathologies and quantification tasks. 35 In conclusion, detectability of liver lesions depended on the radiation dose and phantom size and was considerably improved by selecting the optimal VMI energy. Based on our findings, we suggest VMI at 65 or 70 keV as the optimal VMI energy to detect hypoattenuating or hyperattenuating liver lesions.…”
Section: Discussionmentioning
confidence: 93%
“…found similar results investigating the potential of PCCT for low-dose quantitative spectral tasks in a recent phantom study. They reported comparable iodine quantification accuracy between standard and low radiation doses on PCCT when outperforming accuracy on dual-energy CT. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…There is hope for further improvement in this field as PCCT scanners develop. In DECT, a scanner obtains two sources of information (e.g., by dual X-ray tubes with different voltages); a PCCT scanner can gain even more information by establishing more than two energy thresholds during the separation of detected photons [ 51 ]. The VMIs produced by PCCT scanners have been extensively studied as they are expected to have improved spatial resolution and lower image noise with no need for a higher radiation dose.…”
Section: Postprocessing Techniquesmentioning
confidence: 99%
“…Many studies found that PCCT produces higher-quality VMIs than DECT scanners at low radiation doses [ 52 , 53 ]. Vrbaski et al [ 51 ] reported that PCCTs have comparable accuracy in VMI imaging between low and standard radiation dose levels, whether or not the DECT performance was dependent on the radiation dose. Liu et al [ 54 ] found that VMIs obtained with PECT in a cardiac phantom for coronary CT with different heart rates had especially high spatial and temporal resolutions with a low applied radiation dose.…”
Section: Postprocessing Techniquesmentioning
confidence: 99%